Rubel trasferowy - Kaliński, Janusz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
Common currency of the member states of Comecon came into existence in 1964, 15 years after the organization itself was created. Transfer ruble had a parity in gold (0,987412 g), but still in essence was just a unit of account. Its character was fundamentally different than that of similar currencies of capitalist states. Transfer ruble did not have basic monetary functions, such as measuring worth, paying for expenses, or accumulating value. It was not exchangeable to gold or any other currency, and the official rate of exchange wasn’t real. The transfer ruble was closely linked to planned mutual exchange of Comecon states. Multilateral clearing between Comecon states, proposed together with introduction of the transfer ruble, never came into existence. Transfer ruble, although a fictional creation, had a real impact on trade relations between Soviet bloc countries. The existence of transfer ruble resulted in different pathologies in trade relations, hindered integration and influenced growing internal and external imbalance of Comecon states.